Case Study 5 - Uganda : Participatory Approaches in Budgeting and Public Expenditure Management - World Bank (Washington, DC, 2012)
Budget allocation alone can be a poor indicator of the quality and quantity of public service delivered on the frontline in countries with weak institutions. While shifting of budgetary resources to priority sectors is a good first step, it is crucial to ascertain where and how the allocated sum gets spent. The 1996 Uganda-World Bank attempt at tracking public expenditure in primary education (and health) has revealed a set of surprising findings, prompting fresh thinking on issues such as service "capture", decentralization, cost efficiency, and accountability. The Public Expenditure Tracking Surveys (PETS), as quantitative exercises separate from, but complementary to qualitative surveys on the perception of consumers on service delivery, have been found to be very influential in highlighting the use and abuse of public money. In the absence of a strong institutional infrastructure to manage information flow, surveys such as the one done in Uganda has been seen to not only provide a realistic portrayal of the status of demand and supply of services but also prompt creation of cost effective mechanisms of public accountability through, for example, information dissemination on resource allocation and use.